2010
DOI: 10.1007/s00436-010-1975-y
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma hominis infection of Trichomonas vaginalis is not associated with metronidazole-resistant trichomoniasis in clinical isolates from the United States

Abstract: Trichomonas vaginalis is a protozoan parasite that is the cause of the most common non-viral sexually transmitted disease, trichomoniasis. Metronidazole and tinidazole are the only drugs approved for treatment of T. vaginalis infections in the USA. However, drug resistance exists and some patients are allergic to these medications. Furthermore, the exact mechanism of metronidazole resistance remains undefined and current testing methods require several weeks before results are available. Identification of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 21 publications
(16 reference statements)
2
25
2
Order By: Relevance
“…After incubation, the plates were examined using an inverted microscope to determine the MIC (minimum inhibitory concentration), the lowest drug concentration at which no motile trichomonads were observed at the end of the incubation period. Low-level resistance was defined as an anaerobic MIC 30-60 µM, moderate-level resistance as 60-120 µM, and high-level resistance as 235 µM or greater as previously described by Butler et al (2010). The end point was confirmed by the failure of non-motile parasites to grow after re-inoculation into drug-free medium (Rabiee et al, 2012).…”
Section: Metronidaloze-susceptibility Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…After incubation, the plates were examined using an inverted microscope to determine the MIC (minimum inhibitory concentration), the lowest drug concentration at which no motile trichomonads were observed at the end of the incubation period. Low-level resistance was defined as an anaerobic MIC 30-60 µM, moderate-level resistance as 60-120 µM, and high-level resistance as 235 µM or greater as previously described by Butler et al (2010). The end point was confirmed by the failure of non-motile parasites to grow after re-inoculation into drug-free medium (Rabiee et al, 2012).…”
Section: Metronidaloze-susceptibility Assaymentioning
confidence: 99%
“…A strong relationship between M. hominis coinfection and metronidazole resistance in vitro was proposed (Xiao et al, 2006). In contrast, a lack of correlation in this association was described (Butler et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…Although the cure rate was high, these drugs demonstrated treatment failure which was normally related to non-compliance because of side effects such as headache, dry mouth, metallic taste, glossitis, and urticaria caused by lengthy treatment or high doses (Garduño-Espinosa et al, 1992;Kapoor et al, 1999;Oxberry et al, 1994), or reinfection (Rocha et al, 2012). Moreover, an increasing number of metronidazole-resistant T. vaginalis isolates have been reported since metronidazole was introduced for the treatment of trichomoniasis in 1959 (Blaha et al, 2006;Butler et al, 2010;Durel et al, 1967;Narcisi & Secor, 1996;Schmid et al, 2001; Upcroft et al, 2006). In addition, the metronidazole-resistant isolates were cross-resistant to other members of the 5-nitrothiazole compounds including ornidazole, tinidazole, nitazoxanide, and furazolidone (Wright et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, metronidazole resistance does occur in isolates with intact ntr4 Tv and ntr6 Tv genes, indicating that multiple resistance mechanisms may be responsible for resistance. For example, one study linked resistance to infection of T. vaginalis by Mycoplasma (16); however, the mechanism by which infection would impart resistance is unclear, and this association was not found in a subsequent study (17). Another study found that infection by a double-stranded RNA virus was associated with a lower mean metronidazole MLC value (2); however, the virus is also strongly associated with population 1, being present in 73% of isolates in this population compared to only 2.5% of isolates in population 2 (18).…”
mentioning
confidence: 99%